Chronic stress and coping mechanisms among nurses in Lango sub‐region, northern Uganda - Amir Kabunga; Eustes Kigongo; Samson Udho; Ann Grace Auma; Ponsiano Okalo; Brenda Apili; Namata Halimah; Viola Nalwoga (Wiley, 2023)
Abstract Aim This study aimed to assess chronic stress and coping mechanisms among nurses in Lango sub‐region, northern Uganda, conducted between May and June 2022. Design Institutional‐based cross‐sectional design conducted between May and June 2022. Methods The study included 498 participants recruited from six health facilities. A 12‐Item Short Form Survey tool was used to collect data on chronic stress, while a researcher‐developed questionnaire was used to collect data on coping strategies. Descriptive statistics, binary logistic regression and multiple regression were conducted for data analysis. A p‐value of 0.05 was considered statistically significant. Results Out of 498 participants, 153 (30.7%) were aged between 31 and 40 years, 341 (68.5%) were female, 288 (57.8%) were married, and 266 (53.4%) had less than Diploma. Of the 498 participants, 351 (70.5%) experienced chronic stress. The protective factors against chronic stress were being married (AOR: 0.132; 95% CI: 0.043-0.408; p < 0.001), optimizing shift length (AOR: 0.056; 95% CI: 0.027-0.115; p < 0.001), religiosity/Spirituality (AOR: 2.750; 95% CI: 1.376-5.497; p = 0.004), and regular exercise and breaks (AOR: 0.405; 95% CI: 0.223-0.737; p = 0.003).